Upaya Meningkatkan Manajemen Waktu Siswa Sekolah Menegah Atas melalui Layanan Bimbingan Klasikal - Sholihah, Muinatus; Awalya, Awalya; Aisyah, Aisyah (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This research aims to find out 1) how students' time management was before the classical guidance service. 2) how students' time management is after the implementation of classical guidance service. 3) whether the implementation of classical guidance services can improve students' time management. The research method used Guidance and Counseling Action Research. This research was conducted at SMA Negeri 9 Semarang, the research subjects amounted to 36 students with the criteria of having moderate time management skills. The research data collection technique was obtained from a time management questionnaire. The data obtained were analyzed using a quantitative description. The results showed an increase in students' time management skills from the initial condition before being given action, namely an average of 63.4 to 70, 8 in cycle I and in cycle II to 84.4. Based on these results, it can be stated that there is a significant increase in the time management skills of students in class XI-4 at SMA Negeri 9 Semarang between the pre-cycle of action with cycle I or cycle II.